2020
DOI: 10.3390/nu12113327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ability of Diet-Tracking Mobile Applications to Estimate Energy and Nutrient Intake in Japan

Abstract: We evaluated the energy and nutrient intake estimates of popular Japanese diet-tracking mobile applications (apps). We identified five diet-tracking apps in the iTunes store during August 2020. A researcher entered the dietary data from a one-day paper-based dietary record (DR) previously obtained from apparently healthy free-living adults (15 males and 15 females; 22–65 years) into each app. The energy and nutrient intakes estimated by the apps were compared with those calculated using the Standard Tables of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…These findings suggest that the digital tools could be feasible for assessing dietary intake limited of energy and the main macronutrients. The outcomes of this study are very close to those of other similar studies comparing apps or web-based 24-HRs [ 26 ]. For example, Faillaize et al and Ferrara et al [ 5 , 9 ] described that the apps selected provided estimates of energy and saturated fat intake comparable to the UK research standard method Dietplan6 version 6.0 and USDA Food Composition Database, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…These findings suggest that the digital tools could be feasible for assessing dietary intake limited of energy and the main macronutrients. The outcomes of this study are very close to those of other similar studies comparing apps or web-based 24-HRs [ 26 ]. For example, Faillaize et al and Ferrara et al [ 5 , 9 ] described that the apps selected provided estimates of energy and saturated fat intake comparable to the UK research standard method Dietplan6 version 6.0 and USDA Food Composition Database, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…In turn, Griffiths, et al [ 22 ] observed that selected mobile apps (MyFitnessPal was the only one in common with our apps) tended to underestimate the intake of most nutrients and that comparative validity of energy calculations to Nutrition Data System for Research (an American Windows-based dietary analysis software) may be better than the estimate for macronutrients. In another study performed in Japan [ 26 ], one of the apps that was analyzed was MyFitnessPal, involved also in our analysis. Japanese researchers indicated that in comparison to other selected apps ( n = 4), MyFitnessPal had greater mean differences and wider limits of agreement.…”
Section: Discussionmentioning
confidence: 99%
“…The primary study outcome is the agreement between the tested apps and the reference method according to the energy (kcal). The calculation of sample size was performed similarly to [ 26 ], assuming beta = 0.2 and alpha = 0.05, and was performed for the Bland-Altman analysis for energy intake agreement assessment. We assumed an expected mean of differences of 0 kcal, an expected standard deviation of differences of 100 kcal, and a maximum allowed difference between methods of 250 kcal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations